The role of legal culture in the development of modern society - Maxkamova Nadira Ulfatdjanovna (Genius Journals, 2022)
Legal culture plays an important role in any aspect of society. Especially in today's modern world, the set of rights and freedoms for everyone is one of the forms of primary education. In this article, the author describes in detail the importance of legal culture and legal consciousness in modern society and its priorities.
Keywords: legal culture; legal consciousness; society; family